SEMANTIC CHARACTERISTICS OF ANGLICISMS IN THE TEACHING LANGUAGE METHODOLOGY - Mustafakulova Zarifa Bahodir kizi (The Conference Hub, 2025)
This research examines the semantic features of Anglicisms in language teaching methodology. Borrowed terms from English expand beyond their original meanings, acquiring additional semantic layers within Uzbek pedagogical discourse. Such expansion reflects the complexity and multidimensionality of educational processes, while also demonstrating the adaptability of national discourse to global educational integration.
Keywords: Anglicisms, methodology, semantic expansion, education, linguistics, innovation, discourse.